2023
DOI: 10.1186/s12870-023-04235-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide comparative analysis of the valine glutamine motif containing genes in four Ipomoea species

Abstract: Background Genes with valine glutamine (VQ) motifs play an essential role in plant growth, development, and resistance to biotic and abiotic stresses. However, little information on the VQ genes in sweetpotato and other Ipomoea species is available. Results This study identified 55, 58, 50 and 47 VQ genes from sweetpotato (I. batatas), I.triflida, I. triloba and I. nil, respectively. The phylogenetic analysis revealed that the VQ genes formed eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Recently, a combined approach was adopted to study both biotic and abiotic stress responses in sweet potatoes and identified the role of IbPIF3.1 TF under drought and Fusarium wilt stresses [ 25 ]. The comparative genome-wide study was performed between four Ipomoea species to evaluate valine glutamine motif-containing genes and found 40 differentially expressed genes (DEGs) referring to various abiotic stresses [ 26 ]. The other genome-wide studies in different Ipomoea species were conducted for important TF families such as NAC ( NAM , ATAF , and CUC ) TFs family [ 27 ], hydroxycinnamate-CoA quinate hydroxycinnamoyl transferase gene family [ 28 ], DNA-binding with one finger (Dof) TF family [ 29 ], myeloblastosis (MYB) gene family [ 30 ], phytochrome-interacting factors [ 25 ], domain of unknown function gene family [ 31 ], two-component system genes [ 32 ], xyloglucan endotransglucosylase/hydrolase gene family [ 33 ], expansin gene family [ 34 ], glycine-rich RNA-binding proteins [ 35 ], WRKY TFs family [ 36 ], zinc-finger domain-containing stress-associated proteins [ 37 ], plant-specific GRAS TFs [ 38 ], APETALA2/ethylene responsive factor (AP2/ERF) TFs family [ 38 ], jasmonate-ZIM (JAZ) TF family [ 39 ], and bZIP TF family [ 10 ].…”
Section: Genome-wide Survey Of Tf Families and Their Response To Vari...mentioning
confidence: 99%
“…Recently, a combined approach was adopted to study both biotic and abiotic stress responses in sweet potatoes and identified the role of IbPIF3.1 TF under drought and Fusarium wilt stresses [ 25 ]. The comparative genome-wide study was performed between four Ipomoea species to evaluate valine glutamine motif-containing genes and found 40 differentially expressed genes (DEGs) referring to various abiotic stresses [ 26 ]. The other genome-wide studies in different Ipomoea species were conducted for important TF families such as NAC ( NAM , ATAF , and CUC ) TFs family [ 27 ], hydroxycinnamate-CoA quinate hydroxycinnamoyl transferase gene family [ 28 ], DNA-binding with one finger (Dof) TF family [ 29 ], myeloblastosis (MYB) gene family [ 30 ], phytochrome-interacting factors [ 25 ], domain of unknown function gene family [ 31 ], two-component system genes [ 32 ], xyloglucan endotransglucosylase/hydrolase gene family [ 33 ], expansin gene family [ 34 ], glycine-rich RNA-binding proteins [ 35 ], WRKY TFs family [ 36 ], zinc-finger domain-containing stress-associated proteins [ 37 ], plant-specific GRAS TFs [ 38 ], APETALA2/ethylene responsive factor (AP2/ERF) TFs family [ 38 ], jasmonate-ZIM (JAZ) TF family [ 39 ], and bZIP TF family [ 10 ].…”
Section: Genome-wide Survey Of Tf Families and Their Response To Vari...mentioning
confidence: 99%